SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA PEGAWAI MENGGUNAKAN METODE KEY PERFORMANCE INDICATOR PADA PT. KAWASAN INDUSTRI WIJAYAKUSUMA (PERSERO) SEMARANG - Sugiharto, Dwi Agung; Saefurrohman, Saefurrohman (Information Technology and Telematics, 2018)
Abstract- PT. Wijayakusuma Industrial Estate (Persero) Semarang or often called PT. KIW in running its operational activities is not only required to prioritize business progress or the use of sophisticated technology. But it also needs to pay attention to its human resources, namely how companies can have assets in the form of human resources that have high discipline and performance that is in line with the needs of the company. Employee performance appraisal method uses the key performance indicator (KPI) method, the system development method used in this research is web engineering consisting of formulation, planning, analysis, engineering using UML, implementation using PHP and MySQL.The final result of this study is the final value is calculated using the KPI value formula - (warning value + absence value) which is used to award employee bonuses with bonus criteria of 15% of basic salary if the KPI value> 90, bonus of 10% of basic salary if the value KPI is between 76 - 90, a bonus of 5% of basic salary if the KPI value is between 50 - 75, besides that the employee does not get a bonus